Fabrication of Nanostructured Platinum with Multilevel Porosity for Low Impedance Biomedical Recording and Stimulation Electrodes. (2015) - Ceyssens, Frederik; Sree, Sreeprasanth Pulinthanathu; Martens, Johan; Puers, Robert
Abstract: We report a new lithography-free technology to fabricate porous metal electrodes with multiple levels of porosity, from macroporous – about 1 μm pore diameter – down to nanoporous – 3 nm diameter. The hierarchical combination of mesopores and nanopores allows deeper layers of the electrode to be better accessible for the liquid the electrode is immersed in, aiming to further reduce the impedance of microscale electrodes for biomedical applications. Up to 1000x reduction in impedance was measured in the first experiments, combined with a 230x increase in charge injection capacity. Next to presenting the new and widely applicable (beyond Pt) fabrication process, this is also the first time hierarchical porosity is used in biomedical electrode fabrication.